Core Endurance Relationships With Athletic and Functional Performance in Inactive People - Santos, Marta Silva; Behm, David G.; Barbado, David; DeSantana, Josimari Melo; Da Silva-Grigoletto, Marzo Edir (Frontiers in Physiology, 2019)
Research regarding the relationship between core muscle endurance and performance is limited. The purpose of this study was to analyze the association between core/trunk endurance and athletic performance. Seventy-four healthy participants between 18 and 45 years old participated in this study (Age: 26.0 ± 6.5 years; Mass: 74.6 ± 12.8 kg; Height: 1.74 ± 0.08 m; BMI: 19.0 ± 6.8 Kg/m2). The core endurance was measured using the McGill protocol, consisting of the following tests: trunk flexion, back extension, and side-bridge. Functional performance was evaluated with push-ups, sit to stand, T-run test, countermovement jump, Yo-Yo test, maximum dynamic strength- one repetition maximum (1RM) and muscle power on the bench press, pull row and leg press. The regression results between the McGill protocol (proxy for core/trunk endurance) and the dependent variables were: 1RM pull row: r² 0.109 with p=0.046; RM bench press: r² 0.149 with p=0.012; RM leg press: r² 0.144 with p=0.013 and power pull row: r² 0.151 with p=0.016; power bench press: r² 0.136 with p=0.026; power leg press: r² 0.122 with p=0.013), push-ups: r² 0.157 with p<0.001, sit to stand: r² 0.198 with p<0,001), functional movement score (FMS): r² 0.209 with p<0.001). Nevertheless, core endurance scores were not able to predict jump ability (r² 0.014, p=0.807) or agility (T-test: 0.036 with p=0.497). In conclusion, core endurance exerted no significant influence the agility and jump performance but influenced the ability to run intermittently, exert maximum power and strength in different actions (push, pull and lift exercises) related to the better quality of movement (FMS).